Archaeology and the debate on the transition from reindeer hunting to pastoralism. - Sommerseth, Ingrid (UiT Norges arktiske universitet, 2011)
The distinctive Sami historical land use concerning reindeer management and settlement of inner Troms, North Norway, is reflected in places with archaeological remains. The insight and knowledge connected with these places can be accessed through oral traditions and place-names where reindeer management is embedded in reindeer knowledge developed over long time spans. Previous distinctions between wild reindeer hunting and pastoral herding can be redefined, since much of the traditional knowledge concerning the wild reindeer (goddi) may have been transferred to the domesticated animals (boazu). The transition from reindeer hunting to pastoralism is a current research focus and archaeological results from inner Troms indicate that several Sami dwellings with árran (hearths) are related to a transitional period from AD 1300 to 1400. This period is marked by a reorganisation of the inland Sami siida (collective communities), and changes in landscape use wherein seasonal cycles and grazing access began to determine the movements of people and their domestic reindeer herds. This reorganisation was a response to both external political relations and the inner dynamic of the Sami communities. The first use of tamed reindeer was as decoys and draft animals in the hunting economy, only later becoming the mainstay of household food supply in reindeer pastoralism, providing insurance for future uncertainties. The formation of the national border between Norway-Denmark and Sweden in 1751 led to extensive changes in the previously trans-national mobility pattern, leading to fragmentation of the old siidas and to a new stage of nomadic pastoral economy.